Prevalence of musculoskeletal symptoms and ergonomic risk assessment among production workers in manufacturing industries - Segar, Ganaswaran (2020)
Production worker’s job in manufacturing industries is one of the occupations that risk to Musculoskeletal Symptoms (MSSs) such as awkward postures, repetition motion, and forceful exertions which as causes to serious musculoskeletal injuries. The aim of this study is to identify the prevalence of MSSs and Ergonomic Risk Factors (ERFs) among production workers. This study was conducted using Nordic Musculoskeletal Questionnaire (NMQ) as an interviewing method while Entire Body Risk Assessment (ENBORA), Rapid Entire Body Assessment (REBA) and Quick Exposure Check (QEC) as a direct observational tool. A total of 252 production workers from various manufacturing industries were selected as samples in this case study. Mostly, the age of production workers working there were between 21-30 years old with a percentage of 62.7%. Based on the NMQ results, it showed that most of the workers dealt with lower back (68.7%), shoulder (52.0%), upper back (51.6%) and hands/wrists (50.8%). For QEC tool, all workers were found to have Moderate exposure level except for the back region which for movement tasks with High exposure level (mean=31.18, SD = 6.604). Based on REBA tool, the risk factors on trunk and upper arm were most experienced by workers which put the REBA risk level in High (mean=9.98, SD = 2.430) meanwhile for ENBORA tool, the production workers experienced Medium exposure level mainly from hand/wrist. Pearson Chi Square test was conducted to determine the correlation between NMQ variables and Ergonomic Risk Level. The results indicated there was association between NMQ variables and Ergonomic Risk Level. In conclusion, the high Ergonomic Risk Level among production workers has significantly contributed to harmful exposure and developments of MSSs. Risk factors such as awkward posture, task duration, repetitive motions and heavy physical work must be avoided. The information from this study also suggested to use REBA tool as best way to assess the level of an ergonomic risks at production in manufacturing industries.